2015
DOI: 10.3390/catal5010349
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Direct Activation of Allylic Alcohols in Palladium Catalyzed Amination Reactions

Abstract: Abstract:We here report a computational approach on the mechanism of allylicamination reactions using allyl-alcohols and amines as the substrates and phosphoramidite palladium catalyst 1a, which operates in the presence of catalytic amount of 1,3-diethylurea as a co-catalyst. DFT calculations showed a cooperative hydrogen-bonding array between the urea moiety and the hydroxyl group of the allyl alcohol, which strengthens the hydrogen bond between the O-H moiety of the coordinated allyl-alcohol and the carbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the realm of homogeneous Pd‐catalyzed direct allylic alkylation, the presence of hydrogen bonds formed between allyl alcohols, the solvent, or additives aids in hydroxyl group removal. [ 31‐34 ] For the heterogeneous Pd 1 /TiO 2 ‐EG system, we posit that localized hydrogen bonding established at the distinct atomically dispersed Pd site can equally facilitate allyl alcohol activation. To investigate this hypothesis, sodium carbonate (NaCO 3 ) was introduced into the reaction system (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…In the realm of homogeneous Pd‐catalyzed direct allylic alkylation, the presence of hydrogen bonds formed between allyl alcohols, the solvent, or additives aids in hydroxyl group removal. [ 31‐34 ] For the heterogeneous Pd 1 /TiO 2 ‐EG system, we posit that localized hydrogen bonding established at the distinct atomically dispersed Pd site can equally facilitate allyl alcohol activation. To investigate this hypothesis, sodium carbonate (NaCO 3 ) was introduced into the reaction system (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…The early C−O bond activation of alcohols have proposed some remarkable breakthroughs as well as appealing reaction mechanisms [48–53] . Although limited by the experimental strategies or computational availability, these DFT findings have inspired the further exploitation of comprehensive and generalized activation solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The early CÀ O bond activation of alcohols have proposed some remarkable breakthroughs as well as appealing reaction mechanisms. [48][49][50][51][52][53] Although limited by the experimental strategies or computational availability, these DFT findings have inspired the further exploitation of comprehensive and generalized activation solutions. This review presents selected mechanistic studies on these aspects of theoretical calculations in recent years, an in-depth discussion of the mechanisms and selectivity of the reactions, and a summary and outlook of the development prospects and potential challenges in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a co-catalyst, the reaction proceeded in 85% yield but low regioselectivity (1.3:1 N2:N1, entry 11). Presumably, the benzotriazole nucleophile is sufficiently acidic to promote the ionization of the allylic alcohol . Whereas tricyclic borinic acid 2b and diphenylborinate precatalyst 2c provided inferior results, screening of arylboronic acids revealed that these species also promoted the N1-selective pathway.…”
mentioning
confidence: 99%